From Hazardous Red Mud Waste to Non-Hazardous Commercial Products - Kilic, Yasemin; Gunay, Esin; Marsoglu, Muzeyyen (CARL HANSER VERLAG, 2014)
Red mud is a waste generated by the aluminium industry and its disposal is a major problem. Red mud waste from Eti Seydisehir aluminium plant of Turkey was considered as a hazardous waste for the environment and human health. The storage of the red mud is difficult due to its high amount of various metal oxides, elements and caustic content. In this study, the environmental compliance tests of the produced construction products of red mud were done and evaluated according to the >Regulation on Regularly Storage of Waste in Turkey Regulation on Regularly Storage of Waste in Turkey<.
Keywords: Materials Science